Vertical Integration, the Reconstituted State and the International Criminal Court: Expanding the Horizons of International Law and Governance - Jones, Adrian L. (My University, 2008)
Established in 1998, the permanent International Criminal Court (ICC) presents fundamental complexities for the concept of state sovereignty, while raising prospects for progressively developing international law and global governance in human security related areas. The Court's distinct history, negotiation and governance properties have significance well beyond international criminal justice. The ICC has broader implications for emerging forms of multilateral and transnational cooperation, the heightened standing and visibility of the individual person within the regulatory and protective precincts of international law, and the evolving role, capacity and disposition of the state in brokering, implementing and enforcing innovative governance arrangements. These analyses cross a number of sub-fields within international relations and global governance scholarship. A transcending dimension of my theoretical approach and intended contributions is the idea of state sovereignty as a meta-constitutive institution that fundamentally structures international law and politics, but is itself subject to subtle normative changes in its qualitative meanings and implications. As an institutional fulfillment of the post-Second World War proceedings at Nuremberg, the ICC strikingly departs from the conventional inter-national law of states. The Court seeks to uphold individual-focused human rights and humanitarian law safeguards, as reflected by the three crimes within its jurisdiction: genocide, war crimes, and crimes against humanity. Its jurisdiction over individual offenders is equally novel. The ICC is 'complementary' to national justice systems, and thus will directly administer justice only when states are demonstrably 'unwilling or unable' to conduct genuine proceedings. This distinct supranational governance format aims to facilitate national legislative and capacity-building measures to enhance the vigilance and effective functioning of domestic legal systems. The Court is the permanent organizational and normative focal point of an emerging program of enforcement and supporting efforts. More broadly, it contributes to the normative ideal and practical realization of a comprehensive and integrated global human security agenda.
Keywords: International Criminal Court; global human security agenda; state sovereignty; international law